2015
DOI: 10.1111/jfpp.12580
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antioxidant Effects ofMoringa oleiferaLam. Extracts in Fish Oil during Storage

Abstract: This study assessed the antioxidant activity of Moringa oleifera Lam. extracts on the oxidative stability of fish oil subjected to conditions of accelerate storage (16 days at 60C) compared with synthetic antioxidants such as tertiary butylhydroquinone (TBHQ) and butylated hydroxytoluene (BHT). Fish oil samples were added with leaves, flowers and seed pod extracts and evaluated for peroxide, hydroperoxides, anisidine and conjugated diene values. Changes in trans‐fatty acid and aldehyde content were also assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(60 reference statements)
4
7
0
Order By: Relevance
“…Our results are similar to those of Nascimento et al. (), where the M. oleifera Lam .‐containing fish oil had lower POV than those with other synthetic antioxidants during storage.…”
Section: Resultssupporting
confidence: 92%
“…Our results are similar to those of Nascimento et al. (), where the M. oleifera Lam .‐containing fish oil had lower POV than those with other synthetic antioxidants during storage.…”
Section: Resultssupporting
confidence: 92%
“…The cheese wrapped with the PSG film with 1% ME had lower POV than the other samples, which indicates that the PSG film with 1% ME effectively inhibited the production of primary lipid oxidation products in the cheese. These results are consistent with those of Nascimento et al (2015), where the ME-containing fish oil had lower POV than those with other synthetic antioxidants during storage.…”
Section: Lipid Oxidation Of Gouda Cheese Wrapped With the Psg Filmsupporting
confidence: 82%
“…3a). The decrease in POV after 12 days was observed may be due to unstable peroxides decomposed to secondary products such as ketones, hydrocarbons, and aldehydes (Nascimento et al 2015). At the end of the storage period, the POVs of the control sample, the cheese wrapped with the PSG film, and the cheese wrapped with the PSG film with 1% ME were 5.37, 4.34, and 3.04 meq peroxide/kg sample, respectively.…”
Section: Lipid Oxidation Of Gouda Cheese Wrapped With the Psg Filmmentioning
confidence: 88%
“…Therefore, compared with the control oil, oil samples treated with ME or BHT conserve a higher amount of polyunsaturated fatty acids after 12 days of storage ( p < 0.05). Previous study have shown that M. oleifera extract had high protective effect of polyunsaturated fatty acids in fish oil, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (Nascimento et al, ). There are two different kinds of mechanism, some polyphenols could inhibit the propagation of radical reactions, while others could prevent the formation of free radicals which initiate the oil oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the antioxidant activity of M. oleifera extract in fish oil during accelerate storage experiment showed that M. oleifera leaves extract had significant protective effect of polyunsaturated fatty acids in fish oil (Nascimento et al, ). The antioxidant activity of M. oleifera extract was owing to the presence of chlorogenic acids, caffeoylquinic acids and flavonoids (Makita, Chimuka, Steenkamp, Cukrowska, & Madala, ).…”
Section: Introductionmentioning
confidence: 99%